A qualitative study among refugee children with anxiety in Kuala Lumpur, Malaysia: the effect of child-centred play therapy on the social-emotional development - Taheri, Melika; Mansor, Mariani; Madon, Zainal (Human Resource Management Academic Research Society, 2021)
Healing a sense of self-acceptance and independence among vulnerable groups via developmental methods is a matter of concern by developmental psychologists. Additionally, Malaysia, as a bridging country, is involved in refugees’ journeys. Thereby, this paper is focused on findings from a study carried out on refugee children. This study aimed to investigate the psychosocial development of refugee children with anxiety through the Child Centered Play Therapy (CCPT) process. Nine Farsi speaking refugee children between the age ranges of 8 to 12 in Kuala Lumpur, Malaysia, have participated in 90 CCPT sessions in Sahabat Support Centre. Data were collected on each child’s CCPT session via individual participant observation of the researcher, field notes, video recording and photos taking, alongside participants’ weekly journal entries. Thematic analysis showed that the CCPT process revealed improvement in self, social and emotional development among the respondents. This study proved that CCPT is an effective tool to elevate the suffering of children in one of the most vulnerable group, such as the refugees. Community workers, school teachers, counsellors, and therapists are able to utilize play therapy as an appropriate medium to elevate the children’s suffering and meet their fundamental psychological needs accordingly.